Efficacy of Neutron Radiotherapy for Primary Tracheal Adenoid Cystic Carcinoma: A Single Institution Retrospective Analysis - Shilpen Patel; Christine Y Chon; Laura Tedrick; Joshua K Calvert; Dean Lorimer; Justin R Shinn; Jing Zeng; George E Laramore (Global Journal of Cancer Therapy - Peertechz Publications, 2020)
Background: Primary adenoid cystic carcinoma (ACC) is the second most common primary tracheal neoplasms but the data for optimal treatment plan is limited. This study is an update of our institutional experience treating primary ACC of the trachea with neutron radiotherapy. Methods: Between 1993 and 2012, 33 patients with tracheal adenoid cystic carcinoma were treated with curative intent. Two patients received surgery alone, thirteen received adjuvant neutron radiotherapy post surgical resection, and eighteen received neutron radiotherapy as a primary treatment. Median external beam neutron dose was 19.2 Gy. Two patients who were treated with adjuvant neutron radiotherapy post surgical resection and nine patients treated with neutron radiotherapy alone were also treated with endobronchial brachytherapy boost using high-dose-rate 192Ir source (3.5Gy×2 fractions). Median duration of follow up was 72.4 months (range 0.9-145.9 months) post treatment. Results: Patients who underwent surgery alone, those who received adjuvant neutron radiotherapy post surgical resection, and patients who received neutron radiotherapy as a primary treatment had five-year overall survival rates of 50%, 49% and 93% (p=0.399), and five-year disease-free survival rates of 50%, 58% and 38% (p=0.702) respectively. The five-year overall survival rates and disease free survival rates for patients who received adjuvant high-dose-rate endobronchial brachytherapy in addition to primary treatment as compared to those who did not were 89% and 72% (p=0.489) versus 46% vs 44% (p=0.251) respectively. Conclusions: The data supports the conclusion that adenoid cystic carcinoma of the trachea can be treated with neutron radiation with favorable outcomes.